Correlating Nitrile IR frequencies to local electrostatics quantifies noncovalent interactions of peptides and proteins - Deb, Pranab; Haldar, Tapas; Kashid, Somnath M.; Banerjee, Subhrashis; Chakrabarty, Suman; Bagchi, Sayan (Journal of Physical Chemistry B, 2016)
Noncovalent interactions, in particular the hydrogen bonds and nonspecific long-range electrostatic interactions are fundamental to biomolecular functions. A molecular understanding of the local electrostatic environment, consistently for both specific (hydrogen-bonding) and nonspecific electrostatic (local polarity) interactions, is essential for a detailed understanding of these processes. Vibrational Stark Effect (VSE) has proven to be an extremely useful method to measure the local electric field using infrared spectroscopy of carbonyl and nitrile based probes. The nitrile chemical group would be an ideal choice because of its absorption in an infrared spectral window transparent to biomolecules, ease of site-specific incorporation into proteins, and common occurrence as a substituent in various drug molecules. However, the inability of VSE to describe the dependence of IR frequency on electric field for hydrogen-bonded nitriles to date has severely limited nitrile's utility to probe the noncovalent interactions. In this work, using infrared spectroscopy and atomistic molecular dynamics simulations, we have reported for the first time a linear correlation between nitrile frequencies and electric fields in a wide range of hydrogen-bonding environments that may bridge the existing gap between VSE and H-bonding interactions. We have demonstrated the robustness of this field-frequency correlation for both aromatic nitriles and sulfur-based nitriles in a wide range of molecules of varying size and compactness, including small molecules in complex solvation environments, an amino acid, disordered peptides, and structured proteins. This correlation, when coupled to VSE, can be used to quantify noncovalent interactions, specific or nonspecific, in a consistent manner.

Pick and choose the spectroscopic method to calibrate the local electric field inside proteins - Haldar, Tapas; Kashid, Somnath M.; Deb, Pranab; Kesh, Sandeep; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Electrostatic interactions in proteins play a crucial role in determining the structure function relation in biomolecules. In recent years, fluorescent probes have been extensively employed to interrogate the polarity in biological cavities through dielectric constants or semiempirical polarity scales. A choice of multiple spectroscopic methods, not limited by fluorophores, along with a molecular level description of electrostatics involving solute-solvent interactions, would allow more flexibility to pick and choose the experimental technique to determine the local electrostatics within protein interiors. In this work we report that ultraviolet/visible-absorption, infrared-absorption, or C-13 NMR can be used to calibrate the local electric field in both hydrogen bonded and non-hydrogen bonded protein environments. The local electric field at the binding site of a serum protein has been determined using the absorption wavelength as well as the carbonyl stretching frequency of its natural steroid substrate, testosterone. Excellent agreement is observed in the results obtained from two independent spectroscopic techniques.

Interconverting hydrogen-bonding and weak n -> pi* interactions in aqueous solution: A direct spectroscopic evidence - Deb, Pranab; Jin, Geun Young; Singh, Santosh K.; Moon, Juran; Kwon, Hyejin; Das, Aloke; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry Letters, 2018)
Molecular structure and function depend on myriad noncovalent interactions. However, the weak and transient nature of noncovalent interactions in solution makes them challenging to study. Information on weak interactions is typically derived from theory and indirect structural data. Solvent fluctuations, not revealed by structure analysis, further complicate the study of these interactions. Using 2D infrared spectroscopy, we show that the strong hydrogen bond and the weak n -> pi* interaction coexist and interconvert in aqueous solution. We found that the kinetics of these interconverting interactions becomes faster with increasing water content. This experimental observation provides a new perspective on the existence of weak noncovalent interactions in aqueous solution.

Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Water-controlled keto-enol tautomerization of a prebiotic nucleobase - Datar, Avdhoot; Paithankar, Harshad; Deb, Pranab; Chugh, Jeetender; Bagchi, Sayan; Mukherjee, Arnab; Hazra, Anirban (Journal of Physical Chemistry B, 2022)
Barbituric acid is believed to be a proto-RNA nucleobase that was used for biological information transfer on prebiotic earth before DNA and RNA in their present forms evolved. Nucleobases have various tautomeric forms and the relative stability of these forms is critical to their biological function. It has been shown that barbituric acid has a tri-keto form in the gas phase and an enol form in the solid state. However, its dominant tautomeric form in aqueous medium that is most relevant for biology has been investigated only to a limited extent and the findings are inconclusive. We have used multiple approaches, namely, molecular dynamics, quantum chemistry, NMR, and IR spectroscopy to determine the most stable tautomer of barbituric acid in solution. We find a delicate balance in the stability of the two tautomers, tri-keto and enol, which is tipped toward the enol as the extent of solvation by water increases.